(untitled) (Fiep Bulletin - online, 2011)
Tuberculosis (TB) among the elderly has increased significantly, where the incidence in Brazil has shifted to the elderly population; in 2005 corresponded to 62.79 per 100,000 in Paraiba with an incidence of 52.57 per 100,000 and in Cabedelo the incidence of TB cases reaches alarming percentage in the same period and was considered a priority area for the Program of Tuberculosis Control (PCT). This study aims to characterize the incidence of tuberculosis cases in the elderly population. It’s about a documentary nature, a qualitative approach. Was used as data source for the informations gathered in the database of the Municipal Health Department of Cabedelo, Paraiba, in the period 2005 to 2008. The results points out a significant increase in the incidence of tuberculosis in the elderly population, dealing with a situation of emerging health and complex. This situation requires actions to minimize these data, mostly due to the elderly for being considered a population group of risk for TB, which deserve a special approach of the programs to control the disease, taking in consideration the peculiarities of this age group.